Paths to the discovery of antivenom serotherapy in France - Rosany Bochner (Journal of Venomous Animals and Toxins including Tropical Diseases, 2016)
Abstract The current study presents a descriptive chronological survey of the articles published by Césaire Auguste Phisalix and Albert Calmette on snake poison, with the aim of shedding a light on the areas of research and reasoning followed by these scientists, leading up to their simultaneous discovery of antivenom serotherapy in 1894. The path taken by Phisalix is revealed in 15 articles that demonstrate the motivation of a naturalist and the way he confronted the puzzle of immunity against snake venom. In the case of Calmette, two articles preceded the discovery; microbiology was his theoretical base and the Pasteurian spirit of solving health problems his driving force. These two researchers followed distinct paths, mobilized by different motivations, but produced one single result. It is incontestable that the discovery of antivenom serotherapy was the work of two groups of researchers who deserve equal recognition, but who, in fact, did not receive it. Following the discovery both Calmette and Phisalix returned to their previous motivations. Calmette put the discovery into practice and began to produce antivenom serum in Lille. He came to be generally considered as the sole discoverer of antivenom serotherapy and was the recipient of a number of prestigious prizes. Phisalix, on the other hand, received little recognition and returned to his original interests, devoting himself to research on natural immunity. In Brazil, the discovery of antivenom serum therapy had a profound impact on the work of Vital Brazil Mineiro da Campanha, a researcher known worldwide for his scientific discoveries and for the evidence of the specificity of antivenom serums.